DAMPAK PERUBAHAN PENGGUNAAN LAHAN TERHADAP PEMENUHAN KEBUTUHAN ENERGI LISTRIK DI KABUPATEN KOLAKA TAHUN 2024 - Teguh Budi Raharjo; Ahkmad Yani; Nasrun Kadir (Kohesi: Jurnal Sains dan Teknologi, 2025)
The land-use change phenomenon in Kolaka Regency has significantly impacted electricity demand and supply. This study aims to analyze the relationship between land-use transformation and energy needs, emphasizing the effects of industrial expansion, urbanization, and infrastructure development on electricity consumption. Using a qualitative descriptive approach, data were collected through interviews, field observations, and secondary sources from relevant agencies such as BPS and PLN. The findings reveal that the rapid conversion of agricultural and forest land into industrial and residential areas has led to increased energy consumption, surpassing the available electricity supply. Key challenges include limited power generation capacity, dependency on fossil fuels, and environmental concerns. To address these issues, strategic interventions such as renewable energy development, sustainable land-use policies, and energy efficiency measures are recommended. This study provides valuable insights for policymakers and stakeholders to ensure sustainable energy supply in Kolaka Regency.